Effects of Elaphostrongylus spp. infection on haematology and blood chemistry – in moose (Alces alces), reindeer (Rangifer tarandus), goat (Capra aegagrus hircus) and sheep (Ovis aries) - Engerström, Elin (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2021)
The aim with this study was to investigate the effects Elaphostrongylus alces and Elaphostrongylus rangiferi have on haematology and blood chemistry in experimentally infected animals. The nematodes of genus Elaphostrongylus spp. can cause neurologic disease, myositis, verminous pneumonia and increased mortality. Nine moose (Alces alces) calves, six reindeer (Rangifer tarandus) calves, six goat (Capra aegagrus hircus) kids and five lambs (Ovis aries) were experimentally infected with Elaphostrongylus alces. Three moose calves and one lamb were infected with Elaphostrongylus rangiferi. Each animal was orally inoculated with approx. 1000 infective third-stage larvae, two moose calves received a lower dose (approx. 400 infective larvae, E. alces). Blood samples were taken at around 14-day intervals from each animal and continued until the animal died or was euthanized, 12 to 158 days post inoculation. The blood samples were analysed for haematology and biochemistry parameters including haemoglobin (Hb), haematocrit (HCT), total leukocyte count (LPK), band and segmented neutrophils, eosinophils, basophils, lymphocytes, monocytes, aspartate aminotransferase (ASAT), creatine kinase (CK), glutamate dehydrogenase (GLDH), total protein (TP), urea, cholesterol, calcium, albumin, α1-globulin, α2-globulin, β1-globulin, β2-globulin, γ-globulin and albuminglobulin (A:G) ratio. The analysed parameters from the E. alces and E. rangiferi infected moose calves were compared with results from a control group of six uninfected calves. The six reindeer calves were their own control, comparing samples taken before and after E. alces infection. For the infected goat kids and lambs, changes over time after infection were studied; no samples were taken before infection. The most marked finding in the blood analyses was eosinophilia, significantly elevated in the E. alces infected moose calves, increased also in reindeer calves, goat kids, one lamb, and in E. rangiferi infected moose calves, occurring one to three weeks after infection. ...